Make me a man! : masculinity, Hinduism, and nationalism in India - Banerjee, Sikata (Albany, NY : State University of New York Press, 2005)
"Make Me a Man! argues that ideas about manhood play a key role in building and sustaining the modern nation. It examines a particular expression of nation and manliness: masculine Hinduism. This ideal, which emerged from India's experience of British imperialism, is characterized by martial prowess, muscular strength, moral fortitude, and a readiness to go to battle." "Sikata Banerjee notes that the nationalism defined by masculine Hinduism draws on a more general narrative of nation found in many cultures. If the outcomes of this narrative are to be resisted, the logic of masculinity, armed manhood, and nation need to be examined in diverse contexts."--Jacket
Introduction: constructs of nation and gender -- Empire: Christian manliness and the British gaze -- Nationalism: masculine Hinduism and resisting the British gaze -- Cultural nationalism, masculine Hinduism, and contemporary Hindutva -- In the crucible of Hindutva: women and masculine Hinduism -- Heroic mothers, chaste wives, and celibate warriors: feminist or feminine -- Nationalism in India?
Includes bibliographical references (pages 163-173) and index.
Print version record.
JSTOR
Keywords: Nationalism -- Religious aspects -- Hinduism; Masculinity -- Religious aspects -- Hinduism; Hinduism and state -- India; Nationalism and feminism -- Religious aspects -- Hinduism; Masculinité -- Aspect religieux -- Hindouisme; Hindouisme et État -- Inde; Nationalisme et féminisme -- Aspect religieux -- Hindouisme; PSYCHOLOGY -- Human Sexuality; Nationalism and feminism -- Religious aspects -- Hinduism; Masculinity -- Religious aspects -- Hinduism; Hinduism and state; Nationalism -- Religious aspects -- Hinduism; India